Geographical patterns of body mass distribution are robust even when inserting uncertainty in average estimates of species body mass. (7th July 2017) - Maestri, Renan; Luza, André Luís; de Barros, Lurdiana Dayse; Hartz, Sandra Maria; Ferrari, Augusto; de Freitas, Thales Renato Ochotorena; Duarte, Leandro D. S.
Abstract: Pardiñas, Valenzuela, and Salazar‐Bravo (2017) are concerned that eventual differences in species mean body masses and in the phylogenetic hypothesis used in Maestri et al. (2016)—compared with those available on other potential sources—could affect the results of our original article. Here, we used a new phylogenetic hypothesis to conduct the same analyses of the original article, and we randomly sampled 1000 values of body mass within approximately 35% upper and lower intervals around the mean body mass for each species included in our database. We show that our previous results and conclusions are robust and valid, and they persist despite uncertainty in mean body mass estimation. We argue that sampling variation and uncertainty in both species mean body mass estimation and phylogenetic hypothesis are to be expected and should not always be confused with inaccuracies.